PBL-based STEM: Its effect on the cognitive learning outcome of junior high school students - Kartini, Ayu; Husamah, Husamah; Permana, Fendy Hardian; Mohd Shukri, Ahmad Adnan bin (Universitas Islam Negeri Sumatera Utara, 2023)
The PBL (Problem-based Learning) model based on the STEM approach is very suitable for raising students in the midst of today's increasingly rapid development of the digital era which is based on a problem that encourages students to learn and work cooperatively in groups to find solutions, think critically and analytically, and able to use appropriate learning resources. This study aims to determine the effect of the PBL learning model based on the STEM (Science, Technology, Engineering, and Mathematics) approach to students' cognitive learning outcomes at MTs Muhammadiyah 1 Malang. Sampling with purposive sampling technique. This type of research is a Quasy experiment with a Non-Randomized Control Group Pretest-Postest Design research design. The population in this study were students of class VII MTs Muhammadiyah 1 Malang which consisted of 2 classes. The data analysis technique for cognitive learning outcomes of students uses the data requirements test with the SPSS version 22.0 for Windows program. The collection of research data used an instrument in the form of multiple-choice tests for students' cognitive learning outcomes. Based on the results of hypothesis testing using the ANCOVA test, a sig value of 0.005<0.05 is obtained because the sig value is smaller than 0.05, so it can be said that Ho is accepted which shows that the STEM-based PBL model has a significant influence on students' cognitive learning outcomes. Based on the data obtained, it can be concluded that there is a significant influence in the use of the PBL model based on the STEM approach to students' cognitive learning outcomes at MTs Muhammadiyah 1 Malang.